CONSTRUCTION OF A TELE-LAB PLATFORM FOR THIN FILM ELECTRODEPOSITION USING OPEN-SOURCE DEVICES - Diastama, Krisna
Experimental research of advance materials often requires lab equipment that are limited in number and creates a bottleneck whenever many researcher need to use the same equipment. in-house development of equipment lets the system continously develop and increase capacity for research and education. This research is meant to develop a tele-lab platform for thin film electrodeposition experiments. A Potensiostat and heat controller device is construted using available open-souce designs and connected to a internet of things Node-RED system using MQTT protocol. The system has a voltage range of ±1V, with a standard deviation of 0.6V, a current range of ±100?A with a standard deviation of 0.7?A, and a temperature range of 20ºC-80ºC, with a standard deviation of 2,6ºC. The platform succeded in being used in a electrodeposition experiment, but the devices has problems in accuracy and data transfer that needs further development before it can be used in advance material research.